Analysis of The Implementation of Betta Fish–Assisted Animal Therapy in Reducing Anxiety in Hospitalized Children at Rsui Madinah, Kasembon District - Ahmad Wasis Setyadi; Cyrilla Ayu Pamela; Andan Liries Chopor (International Journal of Health Engineering and Technology, 2026)
Anxiety in hospitalized children is a disturbance of the need for safety and comfort, reflecting inadequate emotional fulfillment, thus requiring adaptation during the treatment process. The purpose of this study is to analyze the implementation of betta fish–assisted animal therapy in reducing anxiety among hospitalized children. This study employed a case study design. The subjects were two hospitalized children experiencing anxiety-related nursing problems in the Wahab Khasbullah Ward at RSUI Madinah Kasembon. Data collection methods included interviews, observations, and documentation using source triangulation. Data analysis was conducted in three stages: (1) data reduction, (2) data display, and (3) conclusion drawing. The nursing evaluation showed that participant 1 (P1) had an anxiety level of HARS scale 12 (no anxiety) and FAS scale 2 (smiling). Meanwhile, participant 2 (P2) had an anxiety level of HARS (mild anxiety) and FAS scale 4 (silent). There was a decrease in anxiety levels among hospitalized children in the Wahab Khasbullah Ward at RSUI Madinah Kasembon after the implementation of betta fish–assisted animal therapy. Animal Assisted Therapy (AAT) provides a combination of care activities involving betta fish, where children imagine that a sick fish, when properly cared for, fed, and kept in a clean environment, can recover quickly and avoid illness.